LEGAL RESPONSES AND CHALLENGES IN ADDRESSING SEXUAL VIOLENCE IN CONTEMPORARY INDONESIAN SOCIETY: A FOCUS ON POLICY GAPS AND VICTIM PROTECTION - Faozi, Safik; Megawati, Wenny (fakultas hukum universitas PGRI Semarang, 2024)
This study critically examines Indonesia’s high rate of sexual violence in relation to modern law. Despite legal efforts, the issue remains alarming. Using a juridical-empirical approach and qualitative-critical-descriptive analysis.The study finds that crime and punishment are rooted in social philosophy. The liberalization of sexual behavior based on consent weakens social, customary, and religious norms, creating a criminogenic environment. This trend is seen in modern countries. Indonesia’s Law Number 12 of 2022 on Sexual Violence Crimes legalizes consensual relations, ignoring customary and religious laws, which fosters a criminogenic atmosphere. Strengthening cultural and religious values is a strategic solution to combat this growing crisis. Sexual violence, often committed by close individuals such as boyfriends, is prevalent in educational institutions, including religious ones. The actual rate of sexual violence is much higher than reported, highlighting the urgent need for effective intervention and cultural reinforcement to address this escalating issue.